Plasmodium chabaudi chabaudi malaria parasites can develop stable resistance to atovaquone with a mutation in the cytochrome b gene - Afonso, Ana Júlia Pinto Fonseca Sieuve (2021)
BACKGROUND Plasmodium falciparum, has developed resistance to many of the drugs in use. The recommended treatment policy is now to use drug combinations. The atovaquone-proguanil (AP) drug combination, is one of the treatment and prophylaxis options. Atovaquone (ATQ) exerts its action by inhibiting plasmodial mitochondria electron transport at the level of the cytochrome bc1 complex. Plasmodium falciparum in vitro resistance to ATQ has been associated with specific point mutations in the region spanning codons 271-284 of the cytochrome b gene. ATQ -resistant Plasmodium yoelii and Plasmodium berghei lines have been obtained and resistant lines have amino acid mutations in their CYT b protein sequences. Plasmodium chabaudi model for studying drug-responses and drug-resistance selection is a very useful rodent malaria model but no ATQ resistant parasites have been reported so far. The aim of this study was to determine the ATQ sensitivity of the P. chabaudi clones, to select a resistant parasite line and to perform genotypic characterization of the cytb gene of these clones. METHODS To select for ATQ resistance, Plasmodium. chabaudi chabaudi clones were exposed to gradually increasing concentrations of ATQ during several consecutive passages in mice. Plasmodium chabaudi cytb gene was amplified and sequenced. RESULTS ATQ resistance was selected from the clone AS-3CQ. In order to confirm whether an heritable genetic mutation underlies the response of AS-ATQ to ATQ, the stability of the drug resistance phenotype in this clone was evaluated by measuring drug responses after (i) multiple blood passages in the absence of the drug, (ii) freeze/thawing of parasites in liquid nitrogen and (iii) transmission through a mosquito host, Anopheles stephensi. ATQ resistance phenotype of the drug-selected parasite clone kept unaltered. Therefore, ATQ resistance in clone AS-ATQ is genetically encoded. The Minimum Curative Dose of AS-ATQ showed a six-fold increase in MCD to ATQ relative to AS-3CQ. CONCLUSIONS A mutation was found on the P. chabaudi cytb gene from the AS-ATQ sample a substitution at the residue Tyr268 for an Asn, this mutation is homologous to the one found in P. falciparum isolates resistant to ATQ.